Modelagem para mensuração do risco tecnológico em ambientes de inovação - Leal, Bruno da Silva (2018)
The knowledge-driven economy, driven by the advancement of technology, provides a dynamic and competitive economic scenario, making organizations look for innovations to stay sustainable over time. Given this, the growing complexity of knowledge and technology makes the interaction between different organizations become a fundamental process for the acquisition of specialized knowledge. Thus, the primordial role of knowledge is strongly associated with innovation as a way to obtain competitive advantages that allow the sustainability of the organization. The best way to achieve competitive advantage is the creation of a unique value, which is preceded by a complex process of acquisition, creation and management of intangible assets. Inserted in this process, the measurement of technological risks, through valuation, is fundamental in the analysis of investments, risks, transfer and commercialization of technologies, which can guarantee sustainability for the organization. For this reason, it is fundamental to establish organizational management methodologies that are allied to the strategy of each business. Thus, the objective of this Dissertation is to propose a modeling that includes concepts of competitiveness and business strategy, intangible assets and innovation, valuation and analytic hierarchy process, giving to the managers a tool for the measurement of technological risks. The modeling was tested in 6 companies residing in an incubator at a federal university in the southern region of the country. The results point to the main organizational risks in general, by capital and by group of intangible assets, as well as for market risk events. The Dissertation presents the application of modeling in companies, suggesting possible actions to seek to minimize the impact generated by each of the risks identified. Data were compiled from all companies participating in the study and analyzed the most recurrent risks and their likely impacts across the universe of companies.